PEMBELAJARAN MATEMATIKA MATERI PENGUKURAN DENGAN MEDIA MONOPOLI MENGGUNAKAN PENDEKATAN MATEMATIKA REALISTIK DI SEKOLAH DASAR - Faradhila, Siska Ayu; Aryanti, Melisa Putri; Zuliana, Eka (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2024)
The aim of this research is to determine the measurement of length and weight of objects using standard units by determining the relationship between standard units that link and estimate the measurement of area and volume using non-standard units and standard units in the form of whole numbers. Based on this matter and background, therefore, improvement in learning is very necessary which is the goal for researchers to realize. In improving learning outcomes, researchers linked realistic mathematics learning models to students in class 3 of SD N Pati Wetan, stages in the learning cycle model. In the learning cycle there are 3 stages, namely the exploration stage, the concept introduction stage, and the concept application stage, after which the results of the data obtained can be analyzed. In the results of this research, the application in this class of the Realistic mathematics learning model can provide an increase in Mathematics learning outcomes for grade 3 students at Pati Wetan 3 Elementary School.